ANALYSIS OF PORE PRESSURE CHARACTERISTICS IN THE NORTH MADURA SUB-BASIN, NORTH EAST JAVA BASIN - Achmad Muwaffaqy, Zhafran
The study area is located in the North Madura Sub-Basin, which is part of the North East Java Basin. Overpressure zones have been identified within this basin. This study investigates the pore pressure characteristics in three wells (BP-1, BT-1, and P-1) using wireline log data, pressure measurement data, and mud weight data to: (1) identify the presence of overpressure zones, (2) determine the distribution of the top of overpressure, (3) analyze the mechanisms responsible for overpressure generation, (4) estimate pore pressure, and (5) evaluate the relationship between the stratigraphy of the study area and the overpressure occurrence. The results reveal that overpressure conditions are observed in all wells, with the top of overpressure at depths ranging from 2,105 ft to 3,050 ft. Overpressure in the study area is attributed to the loading mechanism. The pore pressure gradient within the overpressure zone is estimated to range from 0.434 to 0.865 psi/ft. Overpressure was observed in the Wonocolo, Ngrayong, and Rancak Formations, with variations in the depth of overpressure zones likely controlled by the stratigraphy of the study area, particularly in claystone-dominated formations.